1981
DOI: 10.1002/qua.560200223
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c: Ascorbate reduction site and possible electron‐transfer path

Abstract: The ascorbate reduction reaction of the native and urea-perturbed forms, 0-8M urea, of horse heart ferricytochrome c is found to be a three-step process: a urea-dependent equilibrium step between a reducible and an irreducible form with a midconcentration of urea of 7.4M, a binding step with a binding constant of 5.9M-', and a reduction step with a urea-independent rate constant of 2.9 f 0.3 s-I [J. Biol. Chem. 255,9666 (1980)l. The effect of adding urea, in addition to the generation of an irreducil$e form, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…The higher heme redox potential (E1) was found to be pH-independent in the range 6 Ͻ pH Ͻ 8, which is typical for His/Met-ligated cytochromes c. The observed E1 potential (ϩ183 Ϯ 10 mV, pH 7) is somewhat lower than that of analogues such as cytochrome c (horse heart, ϩ260 mV) (27). In contrast, the second potential (E2) was found to be extremely low (Ϫ479 Ϯ 10mV pH 7) ( Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…The higher heme redox potential (E1) was found to be pH-independent in the range 6 Ͻ pH Ͻ 8, which is typical for His/Met-ligated cytochromes c. The observed E1 potential (ϩ183 Ϯ 10 mV, pH 7) is somewhat lower than that of analogues such as cytochrome c (horse heart, ϩ260 mV) (27). In contrast, the second potential (E2) was found to be extremely low (Ϫ479 Ϯ 10mV pH 7) ( Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…At pH 7 the concentration of the true reductant, i.e. the ascorbate dianion, is very low (26,27) and therefore not expected to interfere with the ET events taking place between the partners of interest. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…201 been extensively studied 19N9). Al-Ayash & Wilson (1979) suggested that dianionic forms of the reductant donate electrons to the exposed haem edge, but more recent work by Myer et al (1980) and provides evidence that ascorbate binds to the arginine-38 residue and that electron transfer to the haem proceeds via aromatic residues.…”
mentioning
confidence: 99%